MANAGEMENT OF SYNCHRONIC LARGE LIVER METASTASIS IN A NON-OCCLUSIVE COLON TUMOR - Eduardo José Brommelstroet Ramos; Hugo Pinto Marques; Martin Palavecino; Timothy Pawlik; Rene Adam; Olivier Soubrane; Paulo Herman; Ricardo Lemos Cotta-Pereira (ABCD: Arquivos Brasileiros de Cirurgia Digestiva)
ABSTRACT In patients with synchronic liver colorectal metastasis, resection of the primary tumor and liver metastases is the only potentially curative strategy. In such cases, there is no consensus on whether resection of the primary tumor and metastases should be performed simultaneously or whether a staged approach should be performed (resection of the primary tumor and after, hepatectomy, or hepatectomy first). Patients with no bowel occlusion and with extensive liver disease are advised neoadjuvant oncological therapy. Similarly, various strategies such as portal vein embolization, liver deprivation, two-staged hepatectomy, and associating liver partition and portal vein ligation are available for patients who do not have a sufficient future liver remnant (generally 30-40% of the total). Therefore, a multidisciplinary approach is required for the treatment of these patients.